Dramaturgy of Women's Leadership Using Facebook Social Media (Case Study: Independent Prosperous Women's Cooperative in Cilegon City, Banten Province) - Laura Irawati; Alfred Inkiriwang; Larasati Simatupang; Marisi Pakpahan (English Lecturers and Teachers Association (ELTA), 2025)
This study explores the dramaturgy of women’s leadership through the use of Facebook as a communication and leadership strategy platform. Focusing on the Independent Prosperous Women's Cooperative in Cilegon City, Banten Province, it examines how female leaders manage impressions and build public images via digital media. Using the ACTORS Theory as an analytical framework, the research applies a dramaturgical approach to analyze how leaders present themselves both in the